PENGARUH IJTIHAD IMAM SYAFIâ€™I TERHADAP PERAN AKAL DALAM PEMBENTUKAN HUKUM ISLAM - Imam Syafiâ€™i; Abdul Aziz (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2022)
Abstract Imam Shafi'i positions human reason in the Istimbat al-Ahkam as a mediation of the 'Aqliyah proposition to reveal the purpose of God in the form of Nash, which sometimes has a relative nature (Dhahir, Mujmal, 'Aam, Mutlaq Etc.) where the mujtahid exploits his mind to reveal Nash's goal is to be grounded. That is in accordance with human expectations on this earth "Maslahah Lil Muslimin Wa al-Muslimah". However, once the role of reason remains in harmony and subject to the texts, this can be seen where Imam Shafi'i does not recognize Istihsan as one of the istinbÃ¢th procedures and also rejects Imam Malik's al-Masalih al-Mursalah. This has an impact on his followers, especially in the position of maá¹£lahah as hujjah as-Syar'iyyah. When maá¹£lahah is considered to be in conflict with texts, ijmÃ¢' or qiyÃ¢s, the Shafi'iyah and HanÃ¢bilah schools are of the opinion that if the maá¹£lahah conflicts with the texts, then what must be prioritized is the text and the position of the maá¹£lahah is not recognized for its validity. Because according to them maá¹£lahah mursalah can be taken later after there is a decision from the texts or fatwas of friends.